2010
DOI: 10.1016/j.coph.2009.09.010
|View full text |Cite
|
Sign up to set email alerts
|

The role of dimerisation in the cellular trafficking of G-protein-coupled receptors

Abstract: The concept that G protein-coupled receptors can exist as homo-and/or hetero-meric complexes is now well established. Despite this, how dynamic such interactions are and if this may be modulated during receptor trafficking remain topics of debate. Use of endoplasmic reticulum trapping strategies and the generation of asymmetric homomers have started to provide information on the contribution of protein-protein interactions to receptor maturation, cell surface delivery and ligand-mediated endocytosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
84
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(86 citation statements)
references
References 53 publications
2
84
0
Order By: Relevance
“…RASSL) b 2 -AR mutant revealed that agonist stimulation of either protomer induced internalization of the dimer (Sartania et al, 2007). Altogether, a discrepancy in the transient nature of at least some GPCR dimers is observed between single molecule labeling strategies and studies demonstrating cointernalization and cotrafficking of receptors (Milligan, 2010).…”
Section: Introductionmentioning
confidence: 96%
“…RASSL) b 2 -AR mutant revealed that agonist stimulation of either protomer induced internalization of the dimer (Sartania et al, 2007). Altogether, a discrepancy in the transient nature of at least some GPCR dimers is observed between single molecule labeling strategies and studies demonstrating cointernalization and cotrafficking of receptors (Milligan, 2010).…”
Section: Introductionmentioning
confidence: 96%
“…Interestingly, the model that dimerization improves the efficiency of delivery at the cell surface is reminiscent of other membrane receptors, including some GPCR proteins. [25][26][27][28][29] In this field, targeting molecular chaperones that regulate GPCRs dimerization and trafficking is a clear novel therapeutic avenue. oligomers complexes and the mechanism of clearance of these fatal species.…”
Section: The Elusive Connection Between Dimerization α-Cleavage and mentioning
confidence: 99%
“…Likewise, dimerization of some GPCRs (i.e. dopamine, opiate or taste receptors) has been shown to alter their pharmacological properties -suggesting that their interaction is stable enough to affect the receptor conformation (Milligan, 2010;Milligan, 2009). Negative cooperativity has been observed between agonists binding to TSH and chemokine receptor dimers (Springael et al, 2005;Urizar et al, 2005)): binding of one agonist ligand to the dimer decreased the affinity of the second agonist by increasing its dissociation rate.…”
Section: Do Gpcrs Function As Monomers or Dimers?mentioning
confidence: 99%
“…In analogy with "family C" receptors, the vast majority of family A and several family B receptors have been shown by BRET or FRET experiments to either dimerize or oligomerize. This idea raised a lot of interest, because the potential consequences of dimerization are so multiple and important (Milligan, 2009;Milligan, 2010;Birdsall, 2010):  Dimerization is essential for "family C" receptor expression at the plasma membrane (Temussi, 2009)) and might play a role in several other systems;  Dimerization affects the "pharmacology" of some receptors. For instance: the sweet taste is sensed by a T1R2-T1R3 heterodimer, while "umami" is detected by a T1R1-T1R3 heterodimer (Temussi, 2009) (NB.…”
Section: Do Gpcrs Function As Monomers or Dimers?mentioning
confidence: 99%